A knot in the protein structure: probing the near-infrared fluorescent protein iRFP designed from bacterial phytochrome - Stepanenko, Olesya V. (2014)
Substantial interest to a family of the bacterial phytochrome photoreceptors (BphPs) is caused by development of near-infrared fluorescent proteins and biosensors, molecularly engineered from BphPs. The near-infrared fluorescent proteins have allowed bioimaging of deep tissues and whole organs noninvasively in living animals. BphPs and derived near-infrared fluorescent proteins contain a structural element, called knot, in their polypeptide chains. Formation of knot structures in proteins was denied for a long time. Here, we studied denaturation and renaturation processes of the near-infrared fluorescent probe, iRFP engineered from RpBphP2, which utilizes a heme-derived tetrapyrrole compound biliverdin as a chromophore. iRFP contains a unique figure-of-eight knot. The denaturation and renaturation curves of the iRFP apoform coincided well, suggesting its efficient refolding. However, the iRFP holoform exhibited the irreversible unfolding and aggregation, associated with the bound chromophore. The knot structure in the apoform did not prevent its subsequent binding of biliverdin, resulting in the functional iRFP holoform. We suggest that the irreversibility of protein unfolding is caused by posttranslational protein modifications, such as chromophore binding, rather than the presence of the knot. These results are important for future design of BphP-based near-infrared probes and add important features to the fundamental problem of protein folding.